Impact of Renal Replacement Therapy on Outcomes of Living Donor Liver Transplantation for Acute Liver Failure: A Cohort Study - Abu Bakar Hafeez Bhatti; Nauman ul Haq; Nayyer Mehmood; Danyal Hassan; Arsalan Ahmed; Wasim Tariq Malik; Haseeb Haider Zia; Mohammad Salih; Nusrat Yar Khan; Abid Ilyas; Nasir Ayub Khan (International Journal of Hepatology)
Despite the promising role of renal replacement therapy (RRT) in acute liver failure (ALF), high-risk patients need liver transplantation and remain at risk for death due to cerebral complications. The objective of this study was to report outcomes of living donor liver transplantation (LDLT) for ALF with perioperative RRT. This was a single-center retrospective cohort study. Out of 1167 LDLTs, 24 patients had ALF and met the King’s College criteria for transplantation. They were categorized into no-RRT (n=13) and RRT (n=11) groups. We looked at 1-year posttransplant survival in these patients. The median serum ammonia level at the time of transplant in the no-RRT and RRT groups was 259.5 mcg/dL (222.7–398) and 70.6 mcg/dL (58.1–92.6) (p=0.005). In the RRT group, serum ammonia level<100 mcg/dL was achieved in all patients. Seven (53.8%) patients in the no-RRT group and 11/11 (100%) in the RRT group were extubated and regained full consciousness after LDLT (p=0.013). The 90-day mortality was 6/13 (46.1%) and 2/11 (18.1%) (p=0.211). There was no brainstem herniation-related mortality in the RRT group, that is, 5/13 (38.4%) and 0/11 (0%) (p=0.030). The 1-year posttransplant survival was also significantly higher in the RRT group (p=0.031). The use of RRT lowers serum ammonia levels and might reduce posttransplant mortality due to brainstem herniation.